Meningkatkan Self Esteem Remaja Melalui Bimbingan Kelompok Dengan Pendekatan Behavioral Therapy - Heppi Sasmita, Neviyarni, Yeni Karneli, Netrawati (Ability: Journal of Education and Social Analysis, 2021)
Self-esteem does not only talk about a person's assessment of himself, but also includes how the individual perceives other people's assessments of him. Therefore, it might happen that adolescents feel that they are capable, but not accompanied by appreciation or recognition from the environment, so that the self-esteem that is formed will be low and ultimately unable to express themselves in a social environment. This study used a quasi-experimental method (quasi experimental design). The design used was a pre-experimental design with one group pre-test and post-test design, using content validity and usingformulas. nonparametric Data analysis was performed using the Wilcoxon Match Pairs Test. The results showed that theZoutput = -2. 812 and Ztable = 1.645. Because the count statistics <table statistics, then Ha is accepted and H0 is rejected. Thus, group counseling guidance with theapproach behavioral therapy was carried out to improve adolescentbehavior self-esteem at the Bundo Saiyo Orphanage, Padang City. This increase has a positive effect on the self-esteem of adolescents so that they are more confident in carrying out activities and learning processes in the future.